Vitamin E, Vitamin C, or Losartan Is Not Nephroprotectant against Cisplatin-Induced Nephrotoxicity in Presence of Estrogen in Ovariectomized Rat Model. (26th September 2012) - Nematbakhsh, Mehdi; Pezeshki, Zahra; Eshraghi-Jazi, Fatemeh; Ashrafi, Farzaneh; Nasri, Hamid; Talebi, Ardeshir; Safari, Tahereh; Haghighi, Maryam; Mansouri, Azam
Abstract : Background . The nephroprotective effect of vitamins E and C or losartan against cisplatin (CP)- induced nephrotoxicity when they are accompanied by estrogen was investigated. Methods . The ovariectomized rats received estradiol valerate for two weeks. At the end of the first week, a single dose of CP (7 mg/kg, IP) was also administered, and they received placebo (group 1), vitamin E (group 2), vitamin C (group 3), or losartan (group 4) every day during the second week, and they were compared with another three control groups. Results . CP alone increased the serum levels of blood urea nitrogen (BUN), creatinine (Cr), and kidney tissue damage score (KTDS), significantly (P < 0.05 ), however at the presence of estradiol and CP, vitamin C, vitamin E, or losartan not only did not decrease these parameters, but also increased them significantly (P < 0.05 ). The serum level of superoxidase dismutase (SOD) was reduced by CP (P < 0.05 ), but it was increased when estradiol or estradiol plus vitamin C or losartan were added (P < 0.05 ). Conclusion . The particular pharmacological dose of estrogen used in this study abolish the nephroprotective effects vitamins C and E or losartan against CP-induced nephrotoxicity.